THE EFFECT OF SERVICE QUALITY ON OUTPATIENT SATISFACTION OF DR. SOEGIRI GENERAL HOSPITAL LAMONGAN - Maya Dewi Hanggraningrum; Tita Hariyanti; Achmad Rudijanto (Jurusan Manajemen Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2017)
Recently, tight competition requires hospitals to provide the best service and quality. Quality services may cause satisfaction to the patient. This study aims to determine the effect of quality service on satisfaction of outpatients at Hospital Dr. Soegiri Lamongan simultaneously and partially. This study utilizes cross sectional approach which involves 235 respondents of simultaneous outpatients. The instrument uses a questionnaire by employing independent and the dependent variables of satisfaction on quality service. The sample was taken by applying proposed sampling method. The data were analyzed using multiple linear regressions. The results of this study indicate that the service quality influence outpatients’ satisfactions.